Water, snow, water : constructive living for mental health - Reynolds, David K. (University of Hawaiʻi Press, 2013)
"You can't be happy all the time. You can't feel comfortable all the time. You can't have the feelings you want when you want them for as long as you want them. Life just doesn't operate like that. Maybe you have tried counseling or therapy or diets or meditation or chemicals or some sort of esoteric magic to work on your feelings, to fix your life or make it perfect. Nothing worked as well as you had hoped. Reading this book won't solve your life problems either. But it will give you some suggestions that are sensible, practical and doable - suggestions about how to work on your life. Work is the key word here. Sitting and talking with someone is not enough. Venting your feelings is not enough. Putting your mind in some quiet inner place is not enough. Working on your life involves moving your body, doing your life purposefully and constructively. This book offers you concrete assignments for such activity." Adapting ideas from Japanese psychotherapies and Eastern thought, Constructive Living (CL) offers a sensible way of living. Across cultures and generations, CL ideas make sound, practical sense. This book presents the state of CL in its application to the West. Using a variety of materials - including essays, tales, maxims, detailed behavioral advice, case studies - the author, the founder of CL, presents fresh perspectives on everything from worrying to love, from psychotherapy to death